RANCANG BANGUN AUTOMATIC TRANSFER SWITCH (ATS) DENGAN METODE SINKRONISASI - Mohammad Wahyusuf Hidayatulloh; Akhmad Zainuri; Onny Setyawati (Jurnal Mahasiswa TEUB, 2023)
Combining Solar power plants electricity sources with PLN electricity sources is expected to save electricity bills because electricity needs are met by two electricity sources, can anticipate the lack of Solar power plants electricity supply, and can anticipate blackouts from PLN electricity sources. For this reason, an automatic control system is needed to switch electricity sources. The control system is the Automatic Transfer Switch (ATS). ATS is equipment that can transfer loads from PLN electricity sources to Solar power plants electricity sources or vice versa automatically if there is a disturbance in one of the electricity sources. This research designs an ATS that is equipped with synchronisation of two power sources using the zero-crossing detector method. The components used are Arduino Mega 2560 Pro Mini as a microcontroller, a voltage detector to detect the voltage of the power source, and 4 10A relays as switches for switching power sources. The result of this research is that there is no delay and wave difference in the load when there is a switch from the PLN power source to the inverter or vice versa. Another condition is that when the PLN power source goes out, the ATS will move the power source automatically to the inverter by only requiring a delay of less than 7 ms to reconnect the power source with the load. Keywords: PLN power source, Solar power plant, ATS, synchronisation.